PSYCHOLOGICAL ANALYSIS OF PARENTS WITH RELAPSE CHILDREN - Safni, Laila Hanum; Misrah, Misrah (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
This study aims to determine the psychological condition of parents who have relapsed children. Relapse is defined as a condition where the old pattern of drug abuse (addiction) returns, where drug use (addiction) returns to drug use. The aim of this research is to determine the psychological condition of parents who have relapsed children. The method used in this research is a qualitative method with a descriptive approach with data collection techniques obtained through interviews, observation and documentation. The research subjects were 2 (two) parents who had relapsed children. The supporting informants in this research were 3 (three) people other than the subjects studied. Cognitive, emotional and interpersonal aspects, namely one subject has a bad psychological condition and the other subject has a good psychological condition. The indicators of success for the two subjects are getting closer to Allah SWT, getting support from family and accepting the situation. It is hoped that the research subjects will continue to accept the fact that the child is experiencing a relapse and will not continue to be sad and that their psychological condition will continue to improve.